The lupus autoantigen La/Ssb is an Xist-binding protein involved in Xist folding and cloud formation. Issue 20 (1st November 2021) - Ha, Norbert; Ding, Nan; Hong, Ru; Liu, Rubing; Roca, Xavier; Luo, Yingyuan; Duan, Xiaowei; Wang, Xiao; Ni, Peiling; Wu, Haiyang; Zhang, Li-Feng; Chen, Lingyi
Abstract: Using the programmable RNA-sequence binding domain of the Pumilio protein, we FLAG-tagged Xist (i nactivated X chromosome s pecific t ranscript) in live mouse cells. Affinity pulldown coupled to mass spectrometry was employed to identify a list of 138 candidate Xist -binding proteins, from which, Ssb (also known as the lupus autoantigen La) was validated as a protein functionally critical for X chromosome inactivation (XCI). Extensive XCI defects were detected in Ssb knockdown cells, including chromatin compaction, death of female mouse embryonic stem cells during in vitro differentiation and chromosome-wide monoallelic gene expression pattern. Live-cell imaging of Xist RNA reveals the defining XCI defect: Xist cloud formation. Ssb is a ubiquitous and versatile RNA-binding protein with RNA chaperone and RNA helicase activities. Functional dissection of Ssb shows that the RNA chaperone domain plays critical roles in XCI. In Ssb knockdown cells, Xist transcripts are unstable and misfolded. These results show that Ssb is critically involved in XCI, possibly as a protein regulating the in-cell structure of Xist .